Review papersAntifungal agents commonly used in the superficial and mucosal candidiasis treatment: mode of action and resistance development - Bondaryk, Małgorzata; Kurzątkowski, Wiesław; Staniszewska, Monika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Recent progress in medical sciences and therapy resulted in an increased number of immunocompromised individuals. Candida albicans is the leading opportunistic fungal pathogen causing infections in humans, ranging from superficial mucosal lesions to disseminated or bloodstream candidiasis. Superficial candidiasis not always presents a risk to the life of the infected host, however it significantly lowers the quality of life. Superficial Candida infections are difficult to treat and their frequency of occurrence is currently rising. To implement successful treatment doctors should be up to date with better understanding of C. albicans resistance mechanisms. Despite high frequency of Candida infections there is a limited number of antimycotics available for therapy. This review focuses on current understanding of the mode of action and resistance mechanisms to conventional and emerging antifungal agents for treatment of superficial and mucosal candidiasis.